PANJANG MULUD DALAM TRADISI MASYARAKAT BANTEN (STUDY KASUS PERAYAAN MAULID NABI DALAM PERSPEKTIF ISLAM) - Marfu'ah, Siti; Fauzan, M Inu (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The Birthday of Prophet Muhammad is one of the great commemorations of Indonesian Muslims. Almost all regions in Indonesia celebrate and carry out the tradition of the prophet's birthday for generations. Mawlid nabi activities in Curuggoong Village, have been carried out for decades and carried out for generations from parents. Curuggoong Village is one of the villages in Padarincang District, Serang Regency, Banten Province. In the activities of the Prophet's Mawlid followed various series of activities, ranging from cleaning the mosque, praying, recitation, eating together, compensation for the poor, giving blessings and procession Long Mulud. Panjang Mulud is a form or container in various forms ranging from ships, planes, cars, boats, mosques, houses or others that are decorated, beautified, beautified and filled with various types of foodstuffs, household furniture, clothes or other fabrics to money. Which will be paraded and distributed to the community. This study aims to find the meaning behind the Long Mulud extension in the celebration of the Prophet's Mawlid in Curuggoong Village. This research uses descriptive methods, and uses qualitative approaches and interviews. After doing so, it was found that Panjang Mulud in Curuggoong was able to survive not only because of tradition but in Panjang Mulud there is a Path to Devotion and Blessings for those who are willing to make it.